Study on Water Erosion Intensity of Soil Slop in Reservoirs under Protection of Tela Anchor Pad - TANG Dingdan; FU Xuhui; WANG Shuo; SONG Yuanyuan; YANG Ming (Renmin Zhujiang, 2020)
The water and soil loss in the hydro-fluctuation belt of the Three Gorges Reservoir has serious adverse effects on the navigation of channel,the stability of reservoir bank and the ecological environment.In view of the problems arisen,this paper proposes a new ecological restoration technology,the Tela anchor pad ecological restoration technology.As an emerging method of slope protection,the Tela anchor pad technology lacks experimental data support in terms of resistance to water erosion before vegetation growth.Therefore,the scouring model test for the slope protection of Tela anchor pad was carried out indoors.The test results show that when the water flow velocity is less than 1.7 m/s,the erosion intensity of the Tela anchor pad is reduced by 91.5% on average compared with the bare slope.